Understanding Trump - Gingrich, Newt (Center Street, 2017)
Understanding Trump requires a willingness to study and learn from him. His principles grow out of five decades of business and celebrity success. Trump behaves differently than traditional politicians because his entire life experience has been different than most traditional politicians. This book will explain the Trump phenomenon and help people understand the emerging movement and administration. Newt Gingrich says President Trump should begin every day by reviewing his campaign promises. Trump owes his presidency to the people who believed in him, not to the courtiers and schmoozers who had contempt for him as candidate but adore him now that he is president.